The Development of Programs to Enhance Creative Leadership Among School Administrators under the Surin Secondary Educational Service Area Office - Fongnual, Nattipong; Noirid, Surachet (Interdisciplinary Academic and Research Journal, 2023)
Creative leadership is developed based on the belief that in a school there may be several leaders who perform a wide range of leadership roles. Leadership roles are therefore not limited to executives only; however, the duty of administrators is to create learning opportunities for teachers and personnel as a channel for such individuals to develop themselves into creative leaders. This research aims to; 1) study current conditions, desirable conditions, and the requirements for enhancing the creative leadership of school administrators and 2) develop a program that will enhance the creative leadership of school administrators. The program consists of three modules, which are 1) the vision module, 2) the flexibility module, and 3) the imagination module. The samples for this study consisted of 300, including school administrators, vice-administrators, and heads of departments. The research instruments were questionnaires, semi-structured interview forms, and evaluation forms as data collection instruments. The collected data were analyzed using measures such as mean, standard deviation, and priority needs index. The findings of the study revealed the following: (1) The current level of creative leadership among school administrators was assessed to be at a medium level overall. On the other hand, the desirable conditions for creative leadership among school administrators were rated at the highest level. The priority needs index that the areas requiring the most attention, ranked from highest to lowest, were vision, flexibility, and imagination. And (2) The program designed to enhance creative leadership among school administrators, as implemented by the Surin Secondary Educational Service Area Office, was evaluated as highly appropriate overall. The possibility for the program was also assessed to be at the highest level.